Kneading Techniques and Settings Breath On Mother Maternity Primigravidae In Dince BPM Safrina Pekanbaru: Kneading Techniques and Settings Breath On Mother Maternity Primigravidae In Dince BPM Safrina Pekanbaru - Rita Afni (Institute Of Computer Science (IOCS), 2020)
Pain in labor is a manifestation of the contraction (shortening) of the uterine muscle. Most mothers perceive and imagine labor pain as a frightening thing or experience. Many mothers are not ready to have children, just because they imagine the pain that will be experienced during childbirth. One way that can be done to reduce pain during labor is to use massage techniques such as kneading techniques and combined with breathing regulation. The aim of this care is to perform midwifery care with kneading techniques and breathing control in primigravida-giving mothers. The method used is to examine a problem through a case consisting of a single unit, namely by doing massage on the back of the mother at the time of contraction and breathing regulation at the time of labor that starts from the active phase. The results obtained after kneading and breath control techniques are based on the assessment of pain experienced by the mother as seen from the facial expression, namely when kneading and breathing techniques are not performed, the maternal pain scale 4 is known and after kneading and breath regulation techniques there is a decrease in the pain scale to 2. In conclusion with the provision of kneading techniques and breathing management to mothers properly and correctly can reduce the pain felt by the mother during labor. It is recommended to midwifery care providers be able to provide information to mothers who want to give birth about how to do kneading techniques and breathing arrangements.